2015
DOI: 10.1016/j.eatbeh.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Low-income women's conceptualizations of food craving and food addiction

Abstract: Food craving and food addiction have been proposed as targets for obesity focused interventions. However, individuals' conceptualizations of these constructs are not well understood and no studies have employed a qualitative approach. Therefore, we sought to understand how women conceptualize food craving and food addiction. Low-income women with preschool-aged children (2-5 years old) participated in either a semi-structured individual interview or focus group in which they were asked about their conceptualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
3
19
1
Order By: Relevance
“…By highlighting qualitative differences between the substance dependence criteria and the characterisation of selfperceived food addiction, the current findings help to explain the previously observed discrepancy between the number of people who fulfil the YFAS criteria and those who self-diagnose (Hardman et al, 2015;Meadows & Higgs, 2013). Furthermore, consistent with other recent qualitative research (Malika et al, 2015), our findings indicate that food addiction is defined within the lay public by a set of core behaviours (as opposed to physical symptoms).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…By highlighting qualitative differences between the substance dependence criteria and the characterisation of selfperceived food addiction, the current findings help to explain the previously observed discrepancy between the number of people who fulfil the YFAS criteria and those who self-diagnose (Hardman et al, 2015;Meadows & Higgs, 2013). Furthermore, consistent with other recent qualitative research (Malika et al, 2015), our findings indicate that food addiction is defined within the lay public by a set of core behaviours (as opposed to physical symptoms).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, several of our participants perceived food addiction to involve a problem with a specific type of food, and consistent with previous research (Ifland et al, 2009;Malika, Hayman, Miller, Lee, & Lumeng, 2015), these were exclusively high-fat and high-sugar foods such as pizza and chocolate. It has been suggested that an inability to control oneself around specific food types provides evidence for the addictive properties of these foods (Schulte, Avena, & Gearhardt, 2015).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings are consistent with those of several quantitative studies of the public acceptance of food addiction, in which participants believed some cases of obesity were a form of addiction with compulsive elements (Lee et al, 2013;Malika, Hayman, Miller, Lee, & Lumeng, 2015).…”
Section: Support For Food Addictionsupporting
confidence: 90%
“…Additionally, it may be that these persons are more sensitive in self‐reporting eating‐related problems, as prior work has also observed that individuals of higher socioeconomic status are more aware of American body ideals and more likely to perceive overweight (Paeratakul, White, Williamson, Ryan, & Bray, ; Wardle et al, ). In contrast, self‐reporting addictive‐like eating behaviour may be more challenging in lower socioeconomic groups, where consumption of highly processed foods may be more frequent due in part to these foods being easily accessible and affordable (Bowman, Gortmaker, Ebbeling, Pereira, & Ludwig, ; Fernandez‐Alvira et al, ; Konttinen, Sarlio‐Lahteenkorva, Silventoinen, Mannisto, & Haukkala, ), and overconsumption of these foods may be viewed as normative (Malika, Hayman Jr., Miller, Lee, & Lumeng, ). This may be comparable to the issues of self‐reporting drinking behaviour within a population where frequent alcohol consumption is normative or socially desirable (e.g., college students) (Baer & Carney, ; Baer, Stacy, & Larimer, ; Del Boca & Darkes, ).…”
Section: Discussionmentioning
confidence: 99%